Corporate cybersecurity : identifying risks and the bug bounty program - Jackson, John (Cybersecurity professional) (John Wiley & Sons, Inc., 2022)
"Understanding the evolution of bug bounty programs first requires familiarity with the hacking landscape, or as many in the information security field know it, penetration testing. Security researchers haven't always been respected nor given the opportunity to shine. Throughout history, hacking has been a word that scares the public and creates waves of fear inside of a company when rumors of a 'hack' spread. The first bounty paid for breaking into something (in recorded history) was in 1851. Charles Alfred Hobbs was paid roughly the equivalent of $20,000 US Dollars to pick a physical lock. (https://www.itspmagazine.com/itsp-chronicles/history-and-interesting-facts-about-bug-bounties-an-appsec-usa-2017-panel-recap)."-- Resumé vydavatel
Keywords: podniky; kyberprostor; kybernetická bezpečnost; zabezpečení počítačových sítí; penetrační testy (počítačová bezpečnost); business enterprises; cyberspace; cyber security; computer network security; penetration tests (computer security); elektronické knihy; monografie; electronic books; monographs